2003
DOI: 10.1007/s00264-003-0515-0
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation in anterior cruciate ligament reconstruction—a histological and biomechanical study on goats

Abstract: We studied reconstruction of the anterior cruciate ligament (ACL) in skeletally mature goats. In one group, the autogenous tissue was augmented with polydioxanone (PDS), the other group had no augmentation. Histological complete incorporation and remodeling of the transplant was found in both groups. The newly formed connective tissues gradually assumed the microscopic properties of the normal ligament. The augmented group showed a delay in remodeling and maturation of the fiber bundles. Mechanically, the PDS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…To circumvent this limitation, a matrix composed of twisted silk fibers has recently been developed as a tissue engineered structure [80][81][82][83][84]. This structure mimics the arrangement of collagen fibers in the ligament and tendon, which has collagen fibers arranged to form fascicles, the fascicles then combine to form the ligament.…”
Section: Methodsmentioning
confidence: 99%
“…To circumvent this limitation, a matrix composed of twisted silk fibers has recently been developed as a tissue engineered structure [80][81][82][83][84]. This structure mimics the arrangement of collagen fibers in the ligament and tendon, which has collagen fibers arranged to form fascicles, the fascicles then combine to form the ligament.…”
Section: Methodsmentioning
confidence: 99%
“…Rapid degradation and loss of mechanical Strength, biologically inert. Acidic degradation By product PDS [95] Common FDA-approved suture material Easily manufactured into diferent forms.…”
Section: Synthetic Polymersmentioning
confidence: 99%
“…Guidoin et al published that ABC surgicraft prostheses were well encapsulated by collagenous tissue which penetrated to the core of the ligament but after surgery it appears to be Anterior Cruciate Ligament Reconstruction associated with high failure rate. The graft was implanted by two diferent techniques and studies have shown that there is no signiicant diference between two graft replacements [95,109] . synovitis and stifness problem was noticed due to particulate debris [96,97,110,111] .…”
Section: Abc Surgicraftmentioning
confidence: 99%
“…Sung and colleagues demonstrated fibroblast attachment and proliferation on scaffolds composed of braided polyglycolic acid (PGA) sutures coated with polycaprolactone (PCL) . Later, a braided polydioxanone (PDS) construct was evaluated in a caprine model but was found to be unsuitable because of the rapid loss of mechanical properties . Lu et al compared braided scaffolds composed of poly l ‐lactic acid (PLLA), PGA, and polylactic‐ co ‐glycolic acid (PLGA).…”
Section: Biomaterials Scaffoldsmentioning
confidence: 99%
“…41 Later, a braided polydioxanone (PDS) construct was evaluated in a caprine model but was found to be unsuitable because of the rapid loss of mechanical properties. 40 Lu et al compared braided scaffolds composed of poly L-lactic acid (PLLA), PGA, and polylactic-co-glycolic acid (PLGA). They concluded that PLLA scaffolds supported the highest rates of ACL fibroblast proliferation and had the most favorable mechanical properties for an ACL substitute.…”
Section: Pcl 43mentioning
confidence: 99%